2022
DOI: 10.1152/ajpendo.00358.2021
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organic pollutants and β-cell toxicity: a comprehensive review

Abstract: Persistent organic pollutants (POPs) are a diverse family of contaminants that show widespread global dispersion and bioaccumulation. Humans are continuously exposed to POPs through diet, air particles, and household and commercial products; POPs are consistently detected in human tissues, including the pancreas. Epidemiological studies show a modest but consistent correlation between exposure to POPs and increased diabetes risk. The goal of this review is to provide an overview of epidemiological evidence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 332 publications
0
10
0
1
Order By: Relevance
“…Furthermore, dioxins are other group of pollutants generates pancreatic β cell dysfunction ( 96 ). There are several mechanisms involved in pancreatic β cell toxicity produced by dioxins that have been reviewed very recently ( 97 ).…”
Section: Effects Of Toxic Metabolites In β Cell Function and Viabilitymentioning
confidence: 99%
“…Furthermore, dioxins are other group of pollutants generates pancreatic β cell dysfunction ( 96 ). There are several mechanisms involved in pancreatic β cell toxicity produced by dioxins that have been reviewed very recently ( 97 ).…”
Section: Effects Of Toxic Metabolites In β Cell Function and Viabilitymentioning
confidence: 99%
“…Some POPs are diabetogenic because they directly modify β-cell function and/or mass ( 31 ). In contrast, other EDCs are nonpersistent, do not accumulate as readily, and are metabolized and excreted in ∼24 h; such EDCs include phthalates and most bisphenols.…”
Section: Endocrine Disrupting Chemicalsmentioning
confidence: 99%
“…Numerous epidemiological studies suggest that POPs exposure may be related to the prevalence of diabetes. In a meta-analysis of six prospective studies, POPs such as total PCBs and HCB were associated with an increased risk of type 2 diabetes . In a recent review, POPs were suggested as a contributing factor causing altered glucose homeostasis and impaired β-cell function in the pancreas . Demographic characteristics might modify the association between POPs exposure and incident diabetes: In a recent meta-analysis, gender-dependency was suggested for associations between POP exposure and incident diabetes .…”
Section: Introductionmentioning
confidence: 99%